IBD Subtype-Regulators IFNG and GBP5 Identified by Causal Inference Drive More Intense Innate Immunity and Inflammatory Responses in CD Than Those in UC - Gao, Sheng; Li, Yichen; Wu, Dingfeng; Jiao, Na; Yang, Li; Zhao, Rui; Xu, Zhifeng; Chen, Wanning; Lin, Xutao; Cheng, Sijing; Zhu, Lixin; Lan, Ping; et al. (Frontiers in Pharmacology, 2022)
Background: The pathological differences between Crohn’s disease (CD) and ulcerative colitis (UC) are substantial, and yet unexplained. Here we aim to identify potential regulators that drive different pathologenesis of CD and UC by causal inference analysis of transcriptome data. Methods: Kruskal-Wallis and Dunnett’s test were performed to identify differentially expressed genes (DEGs) among CD patients, UC patients and controls. Subsequently, differentially expressed pathways (DEPs) between CD and UC were identified and used to construct the interaction network of DEPs. Causal inference was performed to identify IBD subtype-regulators. The expression of the subtype-regulators and their downstream genes were validated by qRT-PCR with an independent cohort. Results: Compared with control group, we identified 1352 and 2081 DEGs in CD and UC groups, respectively. Multiple DEPs between CD and UC were closely related to inflammation related pathways, such as NOD-like receptor signaling, IL-17 signaling and chemokine signaling pathways. Based on the priori interaction network of DEPs, causal inference analysis identified IFNG and GBP5 as IBD subtype-regulators. Results with the discovery cohort showed that the expression level of IFNG, GBP5 and NLRP3 was significantly higher in the CD group than in the UC group. The regulation relationships among IFNG, GBP5 and NLRP3 were confirmed with transcriptome data from an independent cohort and validated by qRT-PCR. Conclusions: Our study suggests that IFNG and GBP5 were IBD subtype-regulators that trigger more intense innate immunity and inflammatory responses in CD than in UC. Our findings reveal pathomechanical differences between CD and UC that may contribute to personalized treatment for CD and UC.